Enhancing the quality of competency assessment for elementary school students in modern education - Lam, Tran Nguyen (International research journal of management, IT and social sciences, 2024)
The paper aims to explore strategies to enhance the quality of competency assessment for elementary school students in the context of modern education. Through a comprehensive study conducted from February 2022 to January 2024 in Hai Phong city, data were collected from 112 educational administrators and 564 teaching professionals. The research employed a mixed-methods approach, combining surveys and interviews to gather insights into current assessment practices and challenges. Findings underscored the critical role of competency assessments in facilitating student development. They revealed a need for tailored assessment methods aligned with contemporary educational standards and student-centered approaches. Additionally, the study highlighted the importance of continuous professional development for educators to improve their assessment literacy and competency evaluation skills. Overall, the research suggests that implementing targeted strategies can lead to more accurate and holistic assessment practices, ultimately fostering student growth and development in elementary education.